Finite-Set Model Predictive Direct Power Control of Grid Connected Current Source Inverter - Feroura, Hamza; Krim, Fateh; Talbi, Billel; Laib, Abdelbaset; Belaout, Abdesslam (Elektronika ir Elektrotechnika, 2017)
This paper proposes a novel control strategy for grid connected current source inverter (CSI) without using a phase locked loop (PLL). The proposed finite set model predictive direct power control (FS-MPDPC) is based on direct power control (DPC) and model predictive control (MPC), and it is introduced for the first time for CSIs. The FS-PDPC controls separately the active and reactive power, using an appropriate discrete-time prediction model to predict the future behaviour of the powers to be injected into the grid, and a cost function for the selection of the optimal control signals to be applied on the switches of the power converter. The proposed control technique is simulated in Matlab/simulink® software. The obtained results verify the effectiveness of this method during different test. DOI: http://dx.doi.org/10.5755/j01.eie.23.5.19240